(untitled) (Research, Society and Development, 2021)
Recently, the protection and treatment of skin diseases with dietary supplements has received increasing attention. One example is collagen peptides that improve skin aging induced by ultraviolet radiation. In this sense, the present work aimed to evaluate the influence of the addition of collagen and sucralose on the technological and sensory characteristics of yogurt through a factorial design with 2 independent variables (X1 = collagen, 0.625 to 1.25% and X2 = sucralose, 0.02 to 0.04%). The dependent variables studied were: total titratable acidity, water holding capacity, acceptance and sweetness. Through the Response Surface methodology, it was observed that the independent variables collagen and sucralose had statistically significant effects (p<0.10) for total titratable acidity and water holding capacity. Total titratable acidity was higher with the increase in collagen and sucralose, and greater water holding capacity was observed between the interaction of collagen and sucralose. The independent variables didn’t influence the acceptance and intensity of sweetness of the samples, being categorized as ideal sweetness and good acceptance. The optimized formulation was obtained with 1.25% collagen and 0.02% sucralose, with a success probability of 88%. Considering the optimized point, a 200g serving of yogurt will contain the recommended amount of collagen per day according to the manufacturer’s information.